O teatro do oprimido como ferramenta educativa: ações junto aos adolescentes em estado de vulnerabilidade social - Silva, Antonio Carlos Barbosa da [UNESP]; Silva, Marina Coimbra Casadei Barbosa da [UNESP]; Nascimento, Cleyton Monteiro [UNESP] (My University, 2014)
This article is a theoretical and practical portrait of a non-formal educational activities aimed to examine the transformations experienced by young people in a state of social vulnerability participating in social discussions in a form of theater of the oppressed - the theater-forum. The technique of theater-forum was held as a methodology able to establish a critical space action / reflection / action on the social reality experienced by these young people. The discussions postulates in some theatrical performances were analyzed critically and scored from theoretical frameworks of contemporary thinkers (Bauman, Augé, Boal,Bock, Aguiar, Ozella). We conclude that this action re-signified social problems (violence, drug involvement, hyperconsumerism, poverty, cultural capital etc.) Among these young people. In general, the young through a collective construction could experience new processes of subjectivity and open to possible changes and social transformations criticism in your life.

O presente artigo é um retrato teórico e prático de uma ação educativa não formal que teve como objetivo analisar as transformações sofridas por jovens em estado de vulnerabilidade social que participaram de debates sociais em uma modalidade do teatro do oprimido – o teatro-fórum. A técnica do teatro-fórum foi defendida como recurso metodológico capaz de estabelecer um espaço crítico de ação/reflexão/ação sobre a realidade social vivenciada por estes jovens. Os debates postulados em algumas encenações teatrais foram analisados de forma crítica e pontuados a partir de referenciais teóricos (Bauman, Augé, Boal, Bock, Aguiar, Ozella). Concluímos que essa ação resignificou as problemáticas sociais (violência, envolvimento com drogas, hiperconsumismo, pobreza, capital cultural etc.) junto a esses jovens. De um modo geral, o jovem através de uma construção coletiva pôde vivenciar novos processos de subjetivação e se abrir para possíveis mudanças e transformações sociais críticas em sua vida.
The teenager redefining its place in contemporary society: The theatre of the oppressed as a tool psychoeducational
Keywords: Adolescence; Subjectivity; Theater of the oppressed; Adolescência; Subjetividade; Teatro do oprimido